“Keep it simple”: the introductions of Veterinary Medicine academic papers - Petry Radünz, Amanda; Cabral, Sara Regina Scotta (Calidoscópio, 2022)
This study investigates the linguistic organization of the introduction sections of academic papers from the Veterinary Medicine field in terms of the two basic systems that determine how one clause is related to another: taxis (degree of interdependency) and logico-semantic relation (Halliday; Matthiessen, 2014, p. 438). All the clauses from the introduction sections of five published academic papers were analyzed. The results showed a high recurrence of simple clauses and embedded clauses in the corpus. In the clause complexes, the preference is for paratactic extensions. The results of this analysis may help understanding the functioning of academic writing in English language in this specific field. Keywords: clause complex; Veterinary Medicine; academic writing.